Deep eutectic solvents: green and sustainable solvents - Jimat, Dzun Noraini (Springer, 2026)
This book highlights the overview of deep eutectic solvents (DESs), their physical and chemical properties for both hydrophilic and hydrophobic types. The multipurpose use of DES in extraction, treatment processes of obtaining value-added products such as organic polymer, biodiesel, active compound or protein from various sources such as biomass, plastics, plant, and animals are discussed. Additionally, this book also includes the impact of its usage on the environment and socio-economic challenges in high scale consumption in various applications as well as its recyclable capability. This book could be a reference for scholars or professionals and students who are involved in this field.